MATURASI INDUK UDANG VANNAMEI (Litopenaeus vannamei) DI BIBIT UNGGUL KALIANDA LAMPUNG SELATAN - Rahmadi; Deyal, Sepin; Nursandi, Juli; Marlina, Eulis (Politeknik Negeri Lampung, 2024)
The availability of broodstock in vannamei shrimp cultivation, especially in hatchery activities, is generally the main requirement. The lack of availability of good quality broodstock is an obstacle in shrimp hatchery activities. One of them is a decrease in egg hatchability which can affect the number and quality of Nauplius produced. Maturation is the initial stage in the process of prospective parent vannamei shrimp becoming mature gonads. Apart from that, the aim of maturation is to maximize growth into adult parent shrimp so that prospective parent vannamei shrimp are ready for spawning. Data collection through observation, documentation, and direct participation in the field in parent maturation activities. The average fecundity produced by each parent during the research ranged from 150-250 thousand eggs. Meanwhile the Hatching Rate was 78.60-79.91%, in December it was 68.37-72.71%. Fertilization Rate (FR) 60-75, Survival of vannamei shrimp in November 91.5%. December 89.5%. The results of water quality measurements, the temperature in the broodstock maturation rearing tank at PT Bibit Unggul Kalianda is around 28-30 oC and the salinity is around 30 ppt.